Genetic variablility of Asian green mussel (Perma viridis) populations in the Philippines - Hulleza, Venice ([Miagao, Iloilo] University of the Phlippines Visayas, 2018)
The Asian green mussel Pernaviridis is considered one of the most economically significant bivalves in the Philippines. The current study aims to analyze genetic variability of mussel populations in the Philippines. P. viridis samples were gathered from Bataan, Cavite and Palawan and genomic DNA was extracted from 25 individual mussel samples per site using standard PCI extraction methods. 18s rRNA genes from the samples was amplified, sent for sequencing and analyzed through Basic Local Alignment Search Tool (BLAST) sequence alignment with reference genes from GenBank, phylogenetic analysis using the Neighbor-Joining method with the Tamura-Nei genetic distance mode, identification of single nucleotide polymorphisms, standard and molecular diversity indices, haplotype diversity and heterozygosity, fixation index (F-statistics) and Tajima?s and Fu?s neutrality tests. Result shows that there is no apparent clustering between and among sequences belonging to different populations, indicative of highly similar sequencies from all three sampling sites. The mussel population from Palawan was observed to have the highest genetic variability exhibiting the highest number of SNPs (102 variants in 48 positions), 60 polymorphic loci, nucleotide diversity (0.216) and haplotype diversity (0.6967). Neutrality tests show that both populations from Bataan are indicative of inbreeding within the population. F-statistics show that Palawan does not exhibit significant genetic differentiation from both sites, suggesting that the Palawan population originated from a transplanted ?parent? population that may have originated from Manila Bay. Populations from Bataan and Cavite however are shown to be significantly different from each other genetically (p=0.001) suggesting that hydrological factors may also contribute to gene flow and differentiation.
Thesis (Master of Science in Biology) -- Miagao, Iloilo : University of the Philippines Visayas, June 2018.
Keywords: Perna viridis; Mussels, Asian Green; Mussels -- Fixation index; Mussels -- Genetic variability